Marconomics : defining economics through social science and consumer behavior - Blawatt, Ken R. (New Delhi, 2016)
Marconomics is about human economics. This text introduces marconomics, examining how the use of the social sciences, consumer behavior in particular, is used to explain and develop economic activity. Blawatt argues the philosophy and principles of the classical school of economic thought are problematic and should be replaced with a new model. He develops a paradigm in the form of two correlated variables that provide the rationale for three economic domains: entrepreneurial, managed, and mass market economies that tell us how business, money, and people work. An economy is a dynamic, behavior-driven structure that is influenced by human variables and exogenous factors that need be included in the creation of models and policies. Marconomics sets an initial framework on which further social scientific research may advance an improved understanding of the discipline.
Keywords: Economics